Un texte et sa continuation : une hypothèse à l’épreuve de quelques expériences stylistiques - Christine Ferlampin-Acher (Perspectives Médiévales)
Artus de Bretagne presents a complex manuscript tradition, which led the author of the article to the hypothesis that the version attested by the oldest witnesses is a version V.I followed by a continuation. The article compares the uses of polysyndeton in the narrative units that constitute the paragraphs of manuscript BnF fr. 761. After ruling out the hypothesis that this internal narrative polysyndeton is a genre style, it is shown that this characteristic is clearly marked in the first part, which is thus stylistically distinguished from the second part. Comparing with other manuscripts suggests that the opposition between the two parts is probably not the work of the copyist of BnF fr. 761. The stylistic approach supports the hypothesis of an allographic continuation.